ChemInform Abstract: Protic Ionic Liquid [TMG][Ac] as an Efficient, Homogeneous and Recyclable Catalyst for One‐Pot Four‐Component Synthesis of 2H‐Indazolo[2, 1‐b]phthalazine‐triones and Dihydro‐1H‐pyrano[2, 3‐c]pyrazol‐6‐ones. Issue 4 (January 2015) - Veisi, Hojat; Manesh, Abbas Amini; Khankhani, Narges; Ghorbani‐Vaghei, Ramin
Abstract The applied catalyst can be recycled at least four times.